The Impact of Resource Exploration and Capital Expenditures on the Realization of Local Government Budgets in Indonesia - Eka Rosalina; Rini Frima; Wiwik Andriani; Ulfah Arima Rm (Yayasan Ilomata, 2023)
This study aims to determine how factors, namely the period of government, gender, government size, and capital expenditure, can affect the realization of the 2018–2021 government budget. This study used a saturated sample consisting of the entire population, namely all provinces in Indonesia for the 2018–2021 period, with a total of 34 provinces, so a sample of 136 was obtained. In this study, the data analysis methods used were descriptive statistics, multiple linear regression analysis, namely the standard effect model, fixed effect model, and random effect model, and hypothesis testing, namely the coefficient of determination test (R2), simultaneous test (F), and partial test (t). The data used are statements of financial position and budget realization reports obtained from the official BPK website, namely https://www.bpk.go.id/ihps. The data were analyzed using STATA v.16 software. Based on the test results, the research results obtained were that the variables of government period and gender did not affect the realization of provincial and local government budgets in Indonesia. Meanwhile, government size and capital expenditure variables affect the realization of provincial government budgets in Indonesia.